Public Health Significance Of Brucellosis In Pigs - Ajay Kumar VJ (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 1998)
Brucellosis is one of the bacterial diseases which affect pigs and produce severe economic loss to the farmers since it causes abortion, still birth, sterility and other complications in pigs. The disease in pigs is also a threat to public health because the etiologic agent can be readily transferred from infected pigs to human beings and can cause the disease in them. Considering the above facts, a serological study was undertaken to assess the extent of the disease present in pigs as well as human beings. During the investigation, serum samples from 255 pigs and 250 human were collected and were subjected to Rose Bengal Plate test (RBPT), Standard tube agglutination test (STAT), Heat inactivation test (HIT), 2 – mecraptoethanol test (2 – MET) and by Ethylene diamine tetra acetate agglutination test (EAT), to detect the presence Brucella agglutinin in these sera. One hundred and seventy samples were collected from slaughtered pigs of which 37 (21.76%) samples gave a positive titre with STAT but only 34 (20% samples had a positive titre by HIT. Twenty seven (15.88%) out of 170 samples gave positive test reaction by RBPT, 2 – MET and EAT. Eighty five samples were collected from the farm reared pigs. Seven (8.24%) of these samples revealed positive agglutination reaction by RBPT, STAT and Hit. 2 – mercaptoethanol test could detect only five (5.88%) of their samples as positive for brucellosis whereas six (7.06%) samples showed positive test reaction by EAT. Out of the 255 serum samples collected from pigs, 26 (10.2%) were found positive with all the tests. Among the 250 human serum samples screened, four of them were found positive for the disease with all the tests. Of the positive samples one male and two female samples were obtained from general population. One of the 88 samples collected from veterinary students was found positive by the tests used in this study. Twenty samples each collected from veterinarians and pig farm attendants were found negative for the disease. Out of all the tests used in this study, STAT was able to detect maximum number of reactors, followed by HIT, RBPT, EAT and finally by 2 – MET. The reasons for differences in seropositivity with different tests on the same sample were discussed.